Investigating the effect of hot and cold polyurethane foam on reducing whole body vibration of forklift operators. - Hajizadeh, Roohalah; Ghiasvand, Fatemeh; Azimi Pirsaraei, Seyed Reza; Khani, Fouzia; Feiz-Arefi, Maryam; Beheshti, Mohammad Hosein (Work, 2024)
BACKGROUND: Vibration is one of the harmful factors for forklift drivers. The use of non- standard seats and not paying attention to how the seats are maintained can be affected by the amount of vibration transmitted to the person. OBJECTIVE: This study investigates the amount of vibration transmitted from the forklift and the effect of different types of polyurethane foam in reducing the vibration transmitted from the forklift seat. METHODS: This descriptive-analytical study was performed on 38 forklifts in 4 diesel models with the same weight class. The amount of vibration transmitted from forklift seats according to ISO2631 standard, taking into account the effect of various factors such as foam type (hot and cold), thickness (6–12 cm), load and year Function was measured. The amount of vibration caused by the forklift on the seat and under the seat was evaluated using ISO7096 standard. RESULTS: The average total vibration of the whole body in all foams in no-load mode is more than with load. The transmission vibration of cold polyurethane foam is less than that of hot polyurethane foam. With increasing thickness, the efficiency of cold polyurethane foam increases by 12 cm and in the loaded state 40.63% and in the unloaded state 49.58% in reducing the vibration transmitted to drivers. CONCLUSION: The results of this study show that cold foam has better effectiveness and efficiency than hot polyurethane foam. Also, the thicker the foam, the less vibration is transmitted to the driver.